Expectations vs. Reality: Nursing Students’ Perspectives on Clinical Learning during the Covid-19 Pandemic - Saban, Rona Beth S.; Balila, Jolly S. (8ISC Proceedings: Covid-19, 2022)
The crisis brought about by the COVID-19 pandemic compelled nursing education providers to make an unprecedented difficult decision to withdraw nursing students from their clinical duties, migrating to an online platform. This study attempts to explore an in-depth view of the nursing students’ experiences in their virtual clinical learning environment during the COVID-19 pandemic, particularly the expectations, challenges, adaptations, and impact. A qualitative phenomenological approach was used in this study, with seven nursing students enrolled during the academic year 2020-2021. Data were gathered using online questionnaires, interviews, and documentation. Responses were analyzed using Braun and Clarke’s (2006) Thematic Analysis. Nine major themes with 23 subthemes emerged. Results revealed that the participants expected exciting possibilities and experiential learning opportunities, but what they have experienced are full online instructional modalities leading to learning constraints primarily due to inadequate skill acquisition. They also experienced a lack of motivation and engagement. The learners adapted through behavioral, academic, and social adaptations, while the teachers coped with problem-focused and emotion-focused strategies. The experience unfolded negative impacts such as future career implications and incompetence; and positive impacts of resilience and lifelong learning. By disclosing these concerns, the researcher aims to underscore the potential challenges that the nursing programs will have to address in the future. In the context of this unparalleled global health emergency, nurse educators must be reminded of their vital responsibilities of preparing individuals who will one day find themselves standing at the frontline. Keywords : nursing education, clinical learning environment, related-learning experience, online learning